DNA Repair genes XRCC1 and OGG1 : Genotoxicity and apoptosis induced by ROS. (2007)
Our genome is constantly exposed to both endogenous and exogenous agents that cause genetic damage. Among the endogenous agents we can find reactive oxygen species (ROS) as cellular metabolism or immune response products (cell to cell genotoxicity). The cellular response to these damages is to repair them or to undergo programmed cell death. DNA repair mechanisms are part of a vital defence system designed to protect the integrity of the genome. Deficiencies in this system most probably lead to cell death or cancer development. There is a wide variability in coding regions of DNA repair genes which may lead to an increased or decrease in repair capability. There is increasing evidence suggesting that a decrease in DNA repair capacity is a consequence of genetic variability and affects cancer susceptibility. Because of all this, the question of interest in our case would be as follows: ¿Does genetic variation in XRCC1 and OGG1 genes affect repair rate and apoptosis induced by endogenous ROS? Our hypothesis is that respiratory burst induces oxidative DNA damage and that this damage activates the base excision repair pathway (BER) and/or apoptosis, therefore, polymorphisms in genes involved in this pathway (XRCC1, OGG1) may affect the inter-individual repair rate of the damage induced by ROS and consequently affect the apoptotic process. In order to correlate these parameters we will determine the allelic frequency of two polymorphisms on gene XRCC1 (Arg194Trp and Arg399Gln), one polymorphism on gene OGG1 (Ser326Cys), and one polymorphism on gene XPD (Lys751Gln) by means of PCR-RFLP in a population of 174 healthy adults belonging to the university community. Secondly, we will obtain two cellular populations (mononuclear and polymorphonuclear cells) from peripheral blood and they will be co-cultured in order to determine repair rates and apoptosis of individuals that bear genetic polymorphisms by means of the Comet Assay and flow cytometry respectively. With this project we expect to establish a relation between polymorphisms in DNA repair genes and both repair and apoptosis events induced by ROS produced by polymorphonuclear (PMN) cells that undergo respiratory burst. According to the results we may be able to reach a genotype-phenotype relation that may allow us to establish the individual susceptibility to ROS-induced cell to cell genotoxicity and consequently to the development of preneoplasic or neoplasic processes; and last but not least, we expect to contribute to the identification of preventive therapeutic intervention targets, once determined which genotypes are more or less efficient in repairing genetic damage induced by endogenous ROS (cell to cell genotoxicity). Resumen Nuestro genoma esta constantemente expuesto a agentes causantes de daño genético tanto endógena como exógenamente. Entre los agentes endógenos se encuentran las especies reactivas de oxígeno como productos del metabolismo celular ó de la respuesta inmune (genotoxicidad célula-célula). La respuesta celular a estos daños es repararlos ó sufrir muerte celular programada. Los mecanismos de reparación del DNA componen un sistema vital de defensa diseñado para proteger la integridad del genoma. Deficiencias en este sistema muy probablemente conducen a la muerte celular o al desarrollo de cáncer. Existe una extensa variabilidad en las regiones codificantes de los genes de reparación del DNA que muy probablemente se traducen en un efecto ya sea de disminución o aumento en la capacidad de reparación. Hay evidencia creciente de que una reducción en la capacidad de reparación del DNA es una consecuencia de la variación genética y afecta la predisposición a cáncer. Con base en lo anterior se plantea la siguiente pregunta: ¿Afecta la variación genética en el gen XRCC1 y OGG1 la tasa de reparación y la apoptosis inducidas por ROS endógenos? Nuestra hipótesis es que la explosión respiratoria induce daño oxidativo en el DNA.